PP028 Hyperhidrosis Quality Of Life Measures: Review And Patient Perspective. (2017) - Jones-Diette, Julie; Wade, Ros; Wright, Kath; Llewellyn, Alexis; Rice, Stephen; Moloney, Eoin; Stoniute, Julija; Layton, Alison; Levell, Nick; Stansby, Gerard; Craig, Dawn; Woolacott, Nerys
Abstract : INTRODUCTION: Primary hyperhidrosis has no discernible cause and is characterised by uncontrollable excessive and unpredictable sweating, which occurs at rest, regardless of temperature. The symptoms of hyperhidrosis can significantly affect quality of life, and can lead to social embarrassment, loneliness, anxiety and depression. The aim of this literature review was to identify the tools used to measure quality of life in studies of hyperhidrosis. Patient advisors provided insight and their perspective. METHODS: Studies were identified through searches undertaken in January 2016. The search strategies combined topic terms for hyperhidrosis with a recognised search filter for "quality of life". All studies that reported measuring quality of life or described a quality of life measure/tool in the context of primary hyperhidrosis were included. The information on the tools and their use in hyperhidrosis was summarized in a narrative synthesis. Patient advisors contributed to the interpretation of the findings. RESULTS: The review included 184 studies and many studies used multiple tools. Twenty-two individual tools were identified. The review identified disease specific, dermatology specific, and general health/utility tools. The most commonly identified tools were the Dermatology Life Quality Index (DLQI), the Hyperhidrosis Disease Severity Scale (HDSS), and the Hyperhidrosis Quality of Life Questionnaire (HQLQ). The Hyperhidrosis Quality of Life index (HidroQoL©) is recently designed and validated, and therefore was used only in its validation study. When asked about these four quality of life tools patient advisors agreed that the HidroQoL© tool covered disease-specific quality of life dimensions relevant to them most comprehensively and was easy to complete. The DLQI was considered to be too general and too focussed on the skin. The HDSS was considered to be too basic and not sufficiently discriminating. CONCLUSIONS: Future studies of the effectiveness of interventions for hyperhidrosis on health-related quality of life may benefit from including the HidroQoL© tool.